Pelatihan Sound System Bagi Anggota Sanggar Kandang Seni Jabung Magetan - Santoso, Iwan Budi; Purnomo, Wahyu (Abdi Seni, 2023)
The artwork community service program was carried out at the Kandang Seni Jabung studio, Jabung Village, Panekan District, Magetan Regency, in the form of workshops/training activities on the use of a sound system to create an album of Jaranan Art Accompaniment Music (Reog) in Magetan Style. Workshops/training activities at the Kandang Seni Jabung art studio use the lecture method and practices of operating sound system equipment. The final result of this artwork community service is to create reliable artists and/or sound-engineer artists to make the music album of the Jaranan Art Accompaniment (Reog) Magetan Style. On the other hand, artists can record and produce music albums. They can also become sound engineers in amplifying the sound of musical performances or other arts that use elements of sounds.